Online Learning in Dental Education: Comparison of Perspectives of Lecturers and Undergraduate Students Between a Public and Private University: A Mixed-Method Study - Kwek Ching Yung; Liong Kah Lok; Budi Aslinie Md Sabri; Fawaz Pullishery; Sobia Bilal; Divya Gopinath (International Journal of Dentistry)
Conclusion: Regardless of the university background, the undergraduates and lecturers were able to adjust to the online learning environment, which mainly reflected a positive perspective on the implementation of online learning. There were modest differences in the perceptions of dental undergraduates between private and public universities, while the perception of the lecturers did not show any difference.